Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects

Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J. (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer